Grandparents, Moms, or Dads? Why Children of Teen Mothers Do Worse in Life - Anna Aizer; Paul J. Devereux; Kjell G. Salvanes (Institute of Labor Economics (IZA), 2020)
Women who give birth as teens have worse subsequent educational and labor market outcomes than women who have first births at older ages. However, previous research has attributed much of these effects to selection rather than a causal effect of teen childbearing. Despite this, there are still reasons to believe that children of teen mothers may do worse as their mothers may be less mature, have fewer financial resources when the child is young, and may partner with fathers of lower quality. Using Norwegian register data, we compare outcomes of children of sisters who have first births at different ages. Our evidence suggests that the causal effect of being a child of a teen mother is much smaller than that implied by the cross-sectional differences but that there are probably still significant long-term, adverse consequences, especially for children born to the youngest teen mothers. Unlike previous research, we have information on fathers and find that negative selection of fathers of children born to teen mothers plays an important role in producing inferior child outcomes. These effects are particularly large for mothers from higher socio- economic groups. Our data also enable us to examine the effect of age at first birth across a range of maternal ages. Importantly, while we find that child outcomes are worst for those born to teen mothers, outcomes improve with mothers' age at first birth until mothers are in their mid-20s and then flatten out.
Keywords: J12; J13; I31; I32; 330; teen childbearing; child outcomes; human capital